Improving Self-Control of High School Students in Padang City (Viewed from the Perspective of Islamic Religious Education) - Batrisyia, Thariyah; Rivauzi, Ahmad (Journal of Multidisciplinary Science: MIKAILALSYS, 2023)
This study examines the improvement of self-control among high school students in Padang City: from the perspective of Islamic religious education. This research aims to explore the efforts of Islamic religious education teachers in enhancing the self-control of students in high schools in Padang City from the perspective of Islamic religious education. The research method used is qualitative with a case study approach. Data were collected through observation, interviews, and documentation. The results of the study indicate that Islamic religious education teachers at SMA Pertiwi 1 Padang make various efforts to improve students' self-control in the aspects of Behavior Control and Cognitive Control. In terms of Behavior Control, teachers use religious activities, character formation through the subject of faith and morals, as well as teaching the moral values of Islam. In terms of Cognitive Control, teachers apply active learning, remedial and enrichment programs, motivation, and student development. The results of this study show that the efforts of Islamic religious education teachers at SMA Pertiwi 1 Padang in improving students' self-control have had a positive impact, as students develop the ability to regulate behavior, control emotions, and make good decisions. Supporting factors in improving students' self-control include well-programmed religious activities, school and teacher support, and a conducive environment. Meanwhile, inhibiting factors include academic pressure, negative peer influence, and an unsupportive environment. This research provides deeper insights and understanding of the efforts of Islamic religious education teachers in improving students' self-control in high schools in Padang City, as well as the supporting and inhibiting factors that influence this process. This study can serve as a reference for further research and provide practical benefits in enhancing students' self-control through an Islamic religious education approach.